2019
DOI: 10.1016/j.ebiom.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant axon branching via Fos-B dysregulation in FUS-ALS motor neurons

Abstract: Background The characteristic structure of motor neurons (MNs), particularly of the long axons, becomes damaged in the early stages of amyotrophic lateral sclerosis (ALS). However, the molecular pathophysiology of axonal degeneration remains to be fully elucidated. Method Two sets of isogenic human-induced pluripotent stem cell (hiPSCs)-derived MNs possessing the single amino acid difference (p.H517D) in the fused in sarcoma ( FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 69 publications
(117 reference statements)
9
45
0
Order By: Relevance
“…FUS mutation causes axonal retention of the FUS protein prior to its aggregation, which is caused by poly(ADP-ribose) polymerase-dependent DNA response signaling (Naumann et al, 2018). The authors of this review also observed the accumulation of mutant FUS protein in the neurites of FUS-mutant induced pluripotent stem cell (iPSC)-derived MNs (Akiyama et al, 2019).…”
Section: Clearance Of Junk Proteinmentioning
confidence: 80%
See 2 more Smart Citations
“…FUS mutation causes axonal retention of the FUS protein prior to its aggregation, which is caused by poly(ADP-ribose) polymerase-dependent DNA response signaling (Naumann et al, 2018). The authors of this review also observed the accumulation of mutant FUS protein in the neurites of FUS-mutant induced pluripotent stem cell (iPSC)-derived MNs (Akiyama et al, 2019).…”
Section: Clearance Of Junk Proteinmentioning
confidence: 80%
“…Increased synaptic activity or branching is considered desirable in the field of psychiatric disease (Shao et al, 2019). The authors of the present review identified aberrant axonal branching in FUS-mutant iPSC-derived MNs (Akiyama et al, 2019). The sensory axons branching in the presence of nerve growth factor (NGF) can be observed at sites marked by stalled mitochondria.…”
Section: Aberrant Axonal Branchingmentioning
confidence: 82%
See 1 more Smart Citation
“…In fact, iPSC-based approaches for studying the pathogenesis of neurological diseases, which are difficult to model with animals, are being explored, and research on therapeutic and preventive agents for such diseases has been accelerated. In particular, dementia including AD [39][40][41], Parkinson's disease [42,43], and ALS [43][44][45][46][47] are among the diseases that are actively studied so that the disease states can be further elucidated and therapeutic agents can be developed for intractable diseases. In terms of neural differentiation methods, the emergence of a neuronal induction method using the transient expression of Ngn2 greatly enhanced neuronal induction efficiencies [8].…”
Section: Discussionmentioning
confidence: 99%
“…FUS knockout mice do not develop ALS-like symptoms or pathology [ 36 38 ], suggesting that loss of FUS function is not sufficient to cause motor neuron diseases. Recent studies using human induced pluripotent stem cells (iPSCs)-derived motor neurons carrying FUS mutations [ 39 41 ], and various mouse models [ 28 , 29 , 34 , 37 , 38 , 42 , 43 ], indicate disease-linked FUS mutations use a “gain of toxicity” mechanism to drive ALS pathogenesis. It is worth mentioning that partial loss of FUS functions such as RNA misprocessing [ 23 , 34 , 44 ], dysfunctional paraspeckles [ 45 ], DNA damage repair [ 43 , 46 , 47 ], mitochondrial dysfunctions [ 48 ] and axonal translation [ 29 ], are also found in these cells and mouse models.…”
Section: Introductionmentioning
confidence: 99%